Penyelesaian Persamaan Painleve Menggunakan Metode Dekomposisi Adomian Laplace - M. Nizam Muhaijir; Wartono Wartono (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
This paper discusses about the solving Painleve equation by using Laplace AdomianDecomposition Method. Laplace Adomian Decomposition Method is a method to solve of nonlinearordinary differential equation that combine between Laplace transform and Adomian DecompositiomMethod. Based on calculation seen that the result that gotten by using Laplace Adomian DecompositionMethod to solve Painleve equation are same with Adomian Decomposition Method. The result thatobtained show the method this is more efecctive and accurate to draw near the exact solution if comparedwith homotopy perturbation method.Keywords : Adomian Decomposition Method, Laplace Adomian Decomposition Method, HomotopyPertubation Method, Painleve Equation.